(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
By treating fabrics with various chemicals under certain conditions, their properties and qualities are changed according to the purpose. Blended fabrics are produced primarily using chemical fibers and threads, the share of which in the total volume of raw materials processed by the textile industry is over 97%, about 3% is natural fibers: silk, cotton and wool, which are used for the production of dress, haberdashery, lining and shirt fabrics. As a result of finishing, yarn yarns will not have the property of being completely wrinkle-free. Therefore, it is desirable to give them the property of low shrinkage. Mixed fiber fabrics containing hydrocellulose and cellulose fibers have sufficient plastic deformation properties. Such mixed fabrics wrinkle quickly. In the final finishing processes, blends of fabrics containing natural and man-made fibers were treated with a sizing compound using Ves Anti Crease SB-38 to achieve a low-crease, low-shrink finish. The effect of finishing agents concentration on the color characteristics of mixed fabrics was studied.